Sex Modifies the Association of Fibroblast Growth Factor 21 With Subclinical Carotid Atherosclerosis - Chee, Yingjie; Toh, Grace Lx; Lim, Chien Joo; Goh, Liuh Ling; Dalan, Rinkoo (Frontiers in Cardiovascular Medicine, 2021)
Background and Aims: Fibroblast growth factor 21 (FGF21), an emerging metabolic hepatokine, is associated with atherosclerosis. An interaction with sex has been described in various populations. We aimed to study whether sex modulates the relationship between FGF21 and subclinical carotid atherosclerosis in a diabetes-enriched multiethnic population of Singapore. We explore differences in intermediary mechanisms, in terms of hypertension, lipids, and inflammation, between FGF21 and atherosclerosis. Methods: We recruited 425 individuals from a single diabetes center in Singapore, and demographics, anthropometry, metabolic profile, FGF21, and carotid ultrasonography were performed. Multivariable logistic regression models were used to study the association between subclinical atherosclerosis and FGF21 adjusting for age, ethnicity, body mass index (BMI), hemoglobin A1c (HbA1c), systolic and diastolic blood pressures, and low-density lipoprotein (LDL)-cholesterol separately for males and females as two groups after an interaction test. Results: An interaction test assessing interaction by sex on the relationship between subclinical atherosclerosis and FGF21 showed a significant interaction with sex (Pinteraction = 0.033). In the female subgroup, significant independent associations of standardized lnFGF21 with subclinical atherosclerosis were seen, with 1 SD increment in lnFGF21 being associated with 1.48-fold (95% CI: 1.03, 2.12; p = 0.036) increase in risk. In the male subgroup, the association of subclinical atherosclerosis with standardized lnFGF21 was not significant [odds ratio (OR) (95% CI): 0.90 (0.63, 1.28); p = 0.553]. We found sex interactions with pulse pressure being significantly associated in females only and triglycerides and C-reactive protein being associated with males only. Conclusion: FGF21 is positively associated with subclinical carotid atherosclerosis in women, but not in men. The sex–racial patterns in the mechanisms by which FGF21 causes subclinical atherosclerosis needs to be explored in larger population-based studies and mechanistically studied in greater detail.